El Gravamen de los Dividendos de Fuente Extranjera y de las Ganancias Derivadas de la Venta de Participaciones en Sociedades no Residentes: La Reforma del Régimen Español en el Marco del Derecho Comparado - Rodríguez Márquez, Jesús (2014)
This paper analyzes the taxation on foreign dividends in comparative tax law. In particular, we study the European and North American system. Finally, we want to assess the Spanish system to avoid international double taxation and its reform, which will be put in force in 2015.